Impact of 5-ALA-induced PPIX accumulation on neural stem cell behavior - Elham Poonaki; Sedra Badlah; Ulf Dietrich Kahlert; Sven G. Meuth; Walter Stummer; Ali Gorji (Brain Research Bulletin)
5-aminolevulinic acid (5-ALA) is a widely recognized and effective tool for improving tumor resections during surgical interventions but may directly interact with cells in the tumor microenvironment. Nevertheless, there remains an ongoing debate regarding the impact of 5-ALA on neural stem cells (NSCs). This study aims to investigate the effects of 5-ALA on both NSCs and oligodendrocyte progenitor cells (OPCs). In this study, NSCs were isolated from the subventricular zones of rat brains and differentiated into OPCs. Both NSCs and OPCs were subsequently treated with 5-ALA, and their effects were evaluated through immunostaining and colony-formation assays. Our findings show that 5-ALA treatment induces PPIX accumulation in both NSCs and OPCs, with NSCs exhibiting higher levels presumably due to their greater proliferation rate. Furthermore, our results indicate that prolonged PPIX accumulation impairs NSC clonogenicity. These results underscore possible interactions of 5-ALA-induced PPIX with NSCs. 5-ALA shows promise as a potential marker for NSCs, but may also be of value for specifically targeting NSCs through activation of porphyrins using light or radiotherapy.